The Role of Teachers in Developing The Interpersonal Skills of Elementary School Students in Pekanbaru - Dewi, Marcella Sari; Ain, Siti Quratul (Jurnal Pendidikan Humaniora, 2024)
This study examines the multifaceted role of teachers in fostering interpersonal skills among 4th-grade students at SDN 42 Pekanbaru. Employing a qualitative approach through naturalistic inquiry, the research aims to provide an in-depth understanding of how teachers contribute to the social and emotional development of students in this context. Data were collected through interviews, observations, and documentation, with analysis conducted using the Miles and Huberman model, which includes data collection, reduction, display, and conclusion drawing. Findings reveal that teachers play diverse roles—as instructors, educators, mentors, coaches, and advisors—in promoting students’ interpersonal skills. As instructors, teachers deliver knowledge and prepare structured lesson plans; as educators, they serve as role models, embodying positive behavior for students to emulate. In the mentor role, teachers guide students throughout the learning process, while as coaches, they assist students in problem-solving and skill development across intellectual, social, and physical domains. Furthermore, teachers act as advisors, encouraging students to engage in positive actions and reinforcing moral values. This comprehensive involvement underscores the significant influence of teachers in shaping students' interpersonal competencies, crucial for their overall growth and social integration.